International Sovereign Bonds by Emerging Markets and Developing Economies : Drivers of Issuance and Spreads - Presbitero, Andrea (IMF Working Papers; Working Paper ;, 2015)
What determines the ability of low-income developing countries to issue bonds in international capital and what explains the spreads on these bonds? This paper examines these questions using a dataset that includes emerging markets and developing economies (EMDEs) that issued sovereign bonds at least once during the period 1995-2013 as well as those that did not. We find that an EMDE is more likely to issue a bond when, in comparison with non-issuing peers, it is larger in economic size, has higher per capita GDP, and has stronger macroeconomic fundamentals and government. Spreads on sovereign bonds are lower for countries with strong external and fiscal positions, as well as robust economic growth and government effectiveness. With regard to global factors, the results show that sovereign bond spreads are reduced in periods of lower market volatility.